2019
DOI: 10.1101/794198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Highly ConservedShhEnhancer Coordinates Hypothalamic and Craniofacial Development

Abstract: Enhancers that are conserved deep in evolutionary time regulate characteristics held in common across taxonomic classes. Here, we deleted the highly conserved Shh enhancer SBE2 (Shh brain enhancer 2) which markedly reduced expression within the embryonic brain specifically in the rostral diencephalon; however, a putative secondary enhancer driving low levels of Shh partially compensated for the loss of SBE2. Further reduction of Shh levels, crossing the SBE2 deletion with the Shh null allele, disrupted brain a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…1C). These defects are consistent with SHH deficiency at early neurulation as seen in Shh mutant mouse embryos (Carreno et al, 2017;Corman et al, 2018;Crane-Smith et al, 2021;Szabo et al, 2009). However, contrary to prior analysis that focused on developmental stages after E9.5, our data uncovered that GAS1 is not required for initial establishment of the SHH domain in the RDVM at E8.5, but to sustain its activity at later stages of neurulation.…”
Section: Discussionsupporting
confidence: 75%
“…1C). These defects are consistent with SHH deficiency at early neurulation as seen in Shh mutant mouse embryos (Carreno et al, 2017;Corman et al, 2018;Crane-Smith et al, 2021;Szabo et al, 2009). However, contrary to prior analysis that focused on developmental stages after E9.5, our data uncovered that GAS1 is not required for initial establishment of the SHH domain in the RDVM at E8.5, but to sustain its activity at later stages of neurulation.…”
Section: Discussionsupporting
confidence: 75%
“…The spatially defined sources of morphogenetic signals, often represented by secreted ligands with long-range action potential (e.g., WNTs, FGFs, BMPs, and Hedgehogs), are referred to as signaling centers or organizers (Figure 1IIIA; Martinez Arias and Steventon, 2018;La Manno et al, 2020). The known signaling centers involved in craniofacial morphogenesis are located in the emerging nervous system, in the foregut endoderm and in spatially defined areas of the facial ectoderm (Marcucio et al, 2005;Wada et al, 2005;Brito et al, 2006;Eberhart et al, 2006;Foppiano et al, 2007;Szabo-Rogers et al, 2008Gitton et al, 2011;Reid et al, 2011;Bhullar et al, 2015;Kaucka et al, 2018;Crane-Smith et al, 2019). Tissueand/or time-specific ablation of morphogens or their sources, such as Sonic Hedgehog (Shh) or the olfactory placodes, showed that the condensations, and in turn the cartilage, are induced by different signaling centers at distinct time points as independent units, pointing at the composite character of the chondrocranium and the future skull (Figures 1 -IIIB,C ;McBratney-Owen et al, 2008;Kaucka et al, 2018).…”
Section: Establishing the Facial Geometry: The Mesenchymal Condensationsmentioning
confidence: 99%